2012
DOI: 10.5435/jaaos-20-06-364
|View full text |Cite
|
Sign up to set email alerts
|

Scapular Dyskinesis and Its Relation to Shoulder Injury

Abstract: The scapula plays a key role in nearly every aspect of normal shoulder function. Scapular dyskinesis-altered scapular positioning and motion-is found in association with most shoulder injuries. Basic science and clinical research findings have led to the identification of normal three-dimensional scapular kinematics in scapulohumeral rhythm and to abnormal kinematics in shoulder injury, the development of clinical methods of evaluating the scapula (eg, scapular assistance test, scapular retraction test), and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
221
1
13

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 301 publications
(240 citation statements)
references
References 32 publications
5
221
1
13
Order By: Relevance
“…Results indicate that for a population of adolescent athletes with an amateur sports level, the dyskinesis prevalence is high; however, it is not associated with pain and does not seem to affect measures of upper limb function. Although some studies support the relationship between pain/ lesion and scapular dyskinesis 2,[7][8][9][10][11] , more than half of the current sample (56.7%) presented changes in scapular movement without, however, being associated with shoulder pain. The results of this study corroborate those of Oliveira et al 28 who analyzed amateur male athletes with shoulder injury syndrome and observed no association between dyskinesis and shoulder pain.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Results indicate that for a population of adolescent athletes with an amateur sports level, the dyskinesis prevalence is high; however, it is not associated with pain and does not seem to affect measures of upper limb function. Although some studies support the relationship between pain/ lesion and scapular dyskinesis 2,[7][8][9][10][11] , more than half of the current sample (56.7%) presented changes in scapular movement without, however, being associated with shoulder pain. The results of this study corroborate those of Oliveira et al 28 who analyzed amateur male athletes with shoulder injury syndrome and observed no association between dyskinesis and shoulder pain.…”
Section: Discussionmentioning
confidence: 89%
“…It has been well documented in the literature that movements at high speed, repetition, and load trigger joint adaptations such as disproportion between internal and external shoulder rotation amplitudes and changes in humeral and scapular positioning [1][2][3][4][5] . Specifically, the modification in the scapula positioning, called scapular dyskinesis, has been studied because it presents possible relations with the presence of pain and shoulder injuries in athletes 2,[6][7][8] . Most of the studies state the relation between shoulder pain/ injury and scapular dyskinesis 2,7,[9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…observation during movement and maximal active humeral elevation, are relevant measures for therapists to use in clinical practice in IwS. Humeral motion can create early scapular motion by placing tension on a shortened glenohumeral capsule or stiff posterior-inferior glenohumeral muscles (Borich et al, 2006;Kibler et al, 2012;Laudner, Moline, & Meister, 2010). Hence, the increase in scapular lateral rotation and presence of anterior tilting and winging seen in IwS with moderate PAF compared to high PAF can be caused by restrictions in posterior glenohumeral structures.…”
Section: Discussionmentioning
confidence: 99%
“…Observation was done from a dorsal and lateral position. Presence of tilting or winging indicated a prominence of the inferior tip of the scapula dorsally or of the medial scapular border, respectively (Kibler, Sciascia, & Wilkes, 2012;Struyf et al, 2009). Palpation was used to verify anatomical landmarks.…”
Section: Test 1: Observation Of Tilting and Wingingmentioning
confidence: 99%